Sliding genioplasty pada penatalaksanaan deformitas dagu - Edi Supriyanto; Asri Arumsari; Bambang A. Sulthana (Journal of Dentomaxillofacial Science, 2009)
Chin contour and position is important component in facial balance. Deformities ofchin may occur as isolation deformity or associated with other dentofacialdeformities. This is a case report of 15-year old girl with chief complaint of chindeformity, and sliding genioplasty has been performed without any complication.